Estudo do processo de soldagem a ponto por fricção de juntas dissimilares entre ligas de alumínio e titânio - Plaine, Athos Henrique (2016)
Multimaterial structures between aluminum and titanium alloys are a technologically attractive field of research and their increasing use in the transportation sector for weight and emission reduction is part of the motivation of this study. The currently used techniques are either too expensive or limited in performance, especially by excessive formation of undesirable intermetallic compounds, opening opportunities for innovation in this area. Friction spot welding (FSpW), a solid state joining process recently developed by Helmholtz Zentrum Geesthacht, has proven to be one of the promising technologies for joining dissimilar materials as it involves short steps and low thermal cycles, also with the advantages of adding no weight to the structure and having geometrical compatibility to replace rivets. The present work studies the feasibility in welding AA5754-H22/Ti6Al4V and AA6181-T4/Ti6Al4V joints through FSpW. In addition, it is intended to establish the microstructure/ properties / process relationships of the resultant joints, in order to understand the formation and growth of the joining interface and its consequences on the mechanical performance. The proposed joints are produced in overlap configuration through different combinations of parameters, which were established by statistical methods involving design of experiments, and later submitted to mechanical and metallurgical characterization. The results reveal that Al/Ti dissimilar joints with high strength and reproducibility can be produced by using FSpW. The mechanical behavior of the joints presents a strong dependence on the intermetallic thickness formed at the bounding interface, identified as TiAl3. Tool rotational speed and dwell time are key process parameters in controlling the resistance of welded joints. Moreover, the bending load associated to differences in stiffness and/or thickness of the welded specimen appears as an important variable influencing the crack propagation path during shear and fatigue tests.